JENIS TUMBUHAN BAWAH OBAT DI BUKIT MAYANA KABUPATEN KUNINGAN - Ade Anwarudin; Ilham Adhya; Nina Herlina (Fakultas Kehutanan dan Lingkungan Universitas Kuningan, 2022)
The understorey was a component of the basic vegetation under forest stands apart from tree regeneration, which consists of grass, herbs and shrubs. Lower plants function to maintain the hydrological cycle, provider of organic matter and maintain soil moisture. Apart from having an ecological function, understorey plants also have benefits for medical purposes that could be developed, one of them was as an ingredient for medicine, both modern and traditional. Knowledge related to medicinal plants was a national asset and national asset that must be utilized and developed also saved because it was very potential to be developed by involving local communities who have knowledge related to these medicinal plants. This research was conducted in Mayana Hill Kuningan Regency, West Java, where this study aimed to determine what types of understorey have the potential as medicine. Retrieval of data in the field used the transects/grid line method, The plot size was 1x1 as well as for an interval between plots of 10 m, with data collection being stopped when there was no more species addition to the sample plots. In the field observations, 41 species of understorey were found, including 28 families and 1041 individuals. Meanwhile, the identification results found that there were 26 species of understorey that have the potential to be medicinal, including 19 families and the number of individuals found as many as 584 individualsTumbuhan bawah merupakan komponen vegetasi dasar di bawah tegakan hutan selain permudaan pohon yang terdiri dari rumput, herba, dan semak. Tumbuhan tingkat rendah berfungsi menjaga siklus hidrologi, penyedia bahan organik dan menjaga kelembaban tanah. Selain mempunyai fungsi ekologis, tumbuhan bawah juga mempunyai manfaat untuk keperluan pengobatan yang dapat dikembangkan, salah satunya sebagai bahan obat baik modern maupun tradisional. Pengetahuan terkait tanaman obat merupakan aset nasional dan aset nasional yang harus dimanfaatkan dan dikembangkan juga dilestarikan karena sangat potensial untuk dikembangkan dengan melibatkan masyarakat lokal yang memiliki pengetahuan terkait tanaman obat tersebut. Penelitian ini dilakukan di Bukit Mayana Kabupaten Kuningan Jawa Barat, dimana penelitian ini bertujuan untuk mengetahui jenis tumbuhan bawah apa saja yang berpotensi sebagai obat. Pengambilan data di lapangan menggunakan metode transek/grid line, ukuran plot 1x1 serta jarak antar plot 10 m, pengambilan data dihentikan bila tidak ada lagi penambahan jenis pada plot sampel. Pada pengamatan di lapangan ditemukan 41 jenis tumbuhan bawah yang terdiri dari 28 famili dan 1041 individu. Sementara hasil identifikasi, terdapat 26 jenis tumbuhan bawah yang berpotensi sebagai obat, termasuk 19 famili dan jumlah individu yang ditemukan sebanyak 584 individu.